Evaluation and thermal performance of cool pavement under desert weather conditions: Surface albedo enhancement and carbon emissions offset - Chaouki Ghenai; Oussama Rejeb; Timothy Sinclair; Naseebah Almarzouqi; Nawal Alhanaee; Federico Rossi (Case Studies in Construction Materials, 2023)
Surfaces such as pavement, buildings, and other heat-absorbing surfaces that store more heat than natural vegetation generate the Urban Heat Island (UHI) effect. Temperatures are known to be significantly higher in urbanized areas compared to rural ones.The application of a reflective surface treatment to the pavement improves its solar reflectivity while lowering the warmth of its surface. The main objective of this study is to assess the performance of a cool pavement in an educational complex parking area, under desert climatic conditions to reduce heat islands. White and high reflective material was applied to the tested parking pavement area. Various experimental techniques were used to assess the performance of non treated (baseline) and treated (cool) pavements including spectral radiation, reflectance (albedo), solar irradiance, and pavement surface temperature. The results show that the coated pavement has a 15 % reflectance in ultraviolet A (UVA) and the untreated pavement has a 17 % solar reflectance (baseline basement). There are no potential dangers to human health posed by the coated pavement's reflection of UVA (For visible wavelengths, coated pavement has a reflectance of roughly 70 %, while uncoated pavement has a reflectivity of only 24 %. Under desert climatic conditions, the results show a net decrease in surface temperature of the coated pavement by up to 15 °C compared to the uncoated one. In the summer, for example, raising the albedo of the pavement surface from 24 % to 70 % lowered the surface temperature from 60 °C to 47 °C. This represents a 22 % decrease in pavement surface temperature. The thermal performance analysis of the cool pavement technology reveals that the pavement surface albedo enhancement will help to increase surface reflectance while lowering pavement surface temperature and offsetting CO2 emissions. Increasing the pavement surface albedo by 192 % (from 24 % to 70 %) for the total treated surface area (81,000 m2) in the educational complex will offset 28,350 tons of CO2. The application of a white coating with a high reflective value on concrete and asphalt pavements will help to extend the life of the pavement, reduce the energy consumption of buildings and the emissions of greenhouse gases, minimize the emissions of carbon dioxide caused by the enhancement of albedo (a strategy for mitigating the effects of climate change), improve parking lot visibility, and deal with the effects of heat islands.